A randomised placebo-controlled clinical trial on the efficacy of local lidocaine injections and oral citalopram for the treatment of complex regional pain syndrome. Issue 3 (March 2022) - Fallico, Nefer; Padmanabhan, Rahul; Rahman, Shakeel; Somma, Francesco; Spagnoli, Anna Maria
Abstract: Background: Complex regional pain syndrome (CRPS) is a neuropathic pain condition with no universally recognised treatment. The study evaluates the efficacy of a therapeutic protocol consisting of oral citalopram and lidocaine injections in patients affected by CRPS. Methods: Between January 2010 and December 2014, 150 consecutive patients with CRPS were enrolled in the study and randomly assigned into three groups: group one – lidocaine injection and oral citalopram; group two – lidocaine injection and oral placebo; and group three – injective and oral placebo. The Impairment Sum Score (ISS) was used to assess the severity of CRPS before, as well as at regular intervals after treatment commenced. Statistical significance ( p  < 0.05) was determined by paired t -tests. Results: The combined treatment proved to be more effective (ISS 47.6 to 12.6) than local anaesthetic alone (ISS 47.5 to 21.5) and to placebo (ISS 47.2 to 29.9). Conclusion: This study indicates that CRPS may be managed with well-tolerated association of oral citalopram and lidocaine injections.